2022
DOI: 10.3390/cells11132002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cognition and Neurogenesis in miR-146b Deficient Mice

Abstract: The miR-146 family consists of two microRNAs (miRNAs), miR-146a and miR-146b, which are both known to suppress a variety of immune responses. Here in this study, we show that miR-146b is abundantly expressed in neuronal cells, while miR-146a is mainly expressed in microglia and astroglia of adult mice. Accordingly, miR-146b deficient (Mir146b-/-) mice exhibited anxiety-like behaviors and enhanced cognition. Characterization of cellular composition of Mir146b-/- mice using flow cytometry revealed an increased n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…We have previously demonstrated that Mir146b-/- mice did not differ from WT animals with regard of body weight, locomotor activity, food and water consumption, hippocampal and total brain volumes at the age of 2-3 months ( 22 ). It is known that systemic administration of LPS in animals leads a behavioral state called “sickness behavior”, which is characterized by lethargy, decreased locomotor activity and appetite, depression-like behavior, and increased sensitivity to pain ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that Mir146b-/- mice did not differ from WT animals with regard of body weight, locomotor activity, food and water consumption, hippocampal and total brain volumes at the age of 2-3 months ( 22 ). It is known that systemic administration of LPS in animals leads a behavioral state called “sickness behavior”, which is characterized by lethargy, decreased locomotor activity and appetite, depression-like behavior, and increased sensitivity to pain ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that treatment of microglial cells with LPS led to increased expression of miR-146b but not miR-146a, while transfection of miR-146b into microglial cells significantly decreased LPS-induced microglial activation and downregulated IRAK1 ( 31 ). Intriguingly, we reported that constitutive miR-146b deficiency didn’t cause microglial activation or signs of neuroinflammation in the hippocampus of the mouse brain ( 22 ). However, knowledge on the regulation of neuroinflammation in the absence of miR-146b is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-146 family consists of the two evolutionarily conserved miRNAs miR-146a and miR-146b (Williams et al 2008 ; Matsumoto et al 2016 ). Since they are expressed in neurons, miR-146a and miR-146b have a role in neuronal development and the control of inflammation in the nervous system (Nguyen et al 2018 ; Chithanathan et al 2022 ). According to one study, gene networks that miR-146a targets are connected to ASD and can be utilized to predict the type and severity of ASD expression in addition to just diagnosing the ASD presence (Nguyen et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In astrocytes, the miR-181 family typically controls neuroinflammatory signaling, and it has been observed that the AD environment increases its expression [ 65 ]. Other than miR-181, numerous miRs, which are involved in AD pathology, including miR-146a [ 66 ], miR-146b [ 67 ], and miR-155 [ 68 ], were elevated in cortical astrocytes of mice following LPS treatment [ 69 ]. The frontal cortex–hippocampal circuitry is involved in learning and memory.…”
Section: The Role Of Astrocytic Micrornas In Multiple Pathways In Admentioning
confidence: 99%